The Study of Social Justice in Pancasila, Islam, and Hinduism Perspective - Mansir, Firman (Universitas Negeri Malang, 2022)
This study aimed to analyze the concept of social justice from Pancasila, Islam and Hinduism perspectives. This study used a qualitative method with literature study techniques to explain ideas related to the concept of justice from Pancasila, Islamic and Hindu perspectives. The concept of justice in Pancasila was defined as a principle that requires all elements, i.e. citizens and the government, to be fair in all areas of life, both material and spiritual, by placing things according to their portion or place without taking sides. Justice in the Islamic perspective could be extracted from QS Al-Baqarah [2]: 148, requiring everyone to compete to do good, known as fastabiqul khairat. Every goodness will, of course, be replaced with a gift. Therefore, justice played a role in giving gifts according to the good that had been done. On the other hand, justice in the Hindu perspective emphasized the balance between the rights obtained and the obligations carried out based on their social position, either individually or collectively.